Applying equity principles leads to higher carbon removal obligations in Canada - Kasra Motlaghzadeh; Neil Craik; Juan Moreno-Cruz; Vanessa Schweizer; Jay Fuhrman; Keith W. Hipel (Communications Earth & Environment)
Abstract Despite net-zero pledges, consensus on national responsibilities for carbon dioxide removal (CDR) strategies is lacking. Here, we use integrated assessment modeling to examine equity-informed estimates of Canada’s remaining carbon budgets, exploring CDR’s role at net-zero and beyond. Gigaton-scale CDR efforts post-2050 are needed to address Canada’s carbon debt under various burden-sharing principles. Cumulative negative emissions (2050-2100) could increase from 7.5 GtCO2 in the Net-Zero scenario to 20.3 GtCO2 in equity-informed scenarios. By 2100, a CDR portfolio, including bioenergy with carbon capture and storage, direct air capture, and enhanced weathering could contribute up to ~500 MtCO2/year of removals. The projected average CDR growth rates, 2.8%-16%/year, align with the historical adoption rates of ammonia synthesis and biomass consumption in Canada, underscoring the importance of drawing lessons from past successes. Socio-economic and technological sensitivity analysis highlights that, despite variations in the role of individual CDR technologies, CDR remains essential for Canada’s post-net-zero commitments.